2017
DOI: 10.1002/jcc.24736
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of excited‐state properties of oligoacene crystals using polarizable continuum model‐tuned range‐separated hybrid functional approach

Abstract: A methodology combining the polarizable continuum model and optimally-tuned range-separated (RS) hybrid functional was proposed for the quantitative characterization of the excited-state properties in oligoacene (from anthracene to hexacene) crystals. We show that it provides lowest vertical singlet and triplet excitation energies, singlet-triplet gap, and exciton binding energies in very good agreement with the available experimental data. We further find that it significantly outperforms its non-tuned RS cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…Theoretical studies of TADF molecules taking into account a solid-state environment have so far been limited. Our group recently developed a methodology, [16][17][18] the polarizable continuum model (PCM) 19 -tuned approach, in which optimal tuning of the range-separation parameter in a longrange corrected functional 16,[20][21][22][23] is combined with the description of the solid-state screening effects via the consideration of the solid-state dielectric constant (ε) in the context of the PCM approach (see Computational Details in the Supporting Information, SI). Our original work has…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies of TADF molecules taking into account a solid-state environment have so far been limited. Our group recently developed a methodology, [16][17][18] the polarizable continuum model (PCM) 19 -tuned approach, in which optimal tuning of the range-separation parameter in a longrange corrected functional 16,[20][21][22][23] is combined with the description of the solid-state screening effects via the consideration of the solid-state dielectric constant (ε) in the context of the PCM approach (see Computational Details in the Supporting Information, SI). Our original work has…”
mentioning
confidence: 99%
“…shown that the accuracy of this methodology in calculating the solid-state ionization potential (IP), electron affinity (EA), transport gap, polarization energy, and exciton binding energy values, is comparable to that of state-of-the-art many-body perturbation theory within the GW approximation, with the results in excellent agreement with experimental data. [16][17][18] In this Letter, we apply this methodology to evaluate the singlet-triplet gap of four representative organic compounds (shown in Figure 1) as a function of the solid-state environment (for the sake of comparison, calculations were also performed with the widely used B3LYP functional). We have considered two TADF donor-acceptor-like molecules, TXO-TPA and TXO-PhCz, see Figure 1, which combine a 9-H-thioxanthen-9-one-10,10-dioxide (TXO) acceptor unit and either triphenylamine (TPA) or N-phenylcarbazole (N-PhCz) as a donor unit; these were taken from the work of Wang et al 7 In addition, we have investigated PXZ-TRZ (10-(4-(4,6-diphenyl-1,3,5triazin-2-yl)phenyl)-10H-phenoxazine), which has been reported to have a very small ΔE ST of ~0.06 eV 6 , as well as CBP (4,4'-bis(carbazol-9-yl)-p-biphenyl), which has a large ΔE ST of ~0.71 eV 6 (we note that CBP is not a TADF molecule and is usually employed as a hole-transporting material in conventional OLEDs).…”
mentioning
confidence: 99%
“…In the gas phase, the optimized system‐dependent parameters of subPC and anthracene are 0.16 and 0.22 Bohr −1 , respectively. Compared to the previous results, the optimized ω of anthracene is almost identical to the value by Sun et al [ 40 ] In addition, for comparison, we also selected the M06HF density functional to calculate the monomer and dimers of anthracene. M06HF is one of the M06 suite of meta‐hybrid generalized gradient approximation density functionals and has 100% Hatree‐Fock (HF) exchange.…”
Section: Methodsmentioning
confidence: 73%
“…This quantity, corresponding to the difference between the electronic gap and the excitation energy, is most accurately estimated from the solution of the BSE [83][84][85][86][87][88][89] on top of the GW approximation for the electronic self-energy. However, mainly due to (partial) error compensation (see details in the SI), TDDFT results obtained with a range-separated hybrid functional can provide a reliable estimate of this quantity [90][91][92][93][94][95][96] for the purpose of this work. In order to corroborate the reliability of our results, a direct comparison between the optical spectra computed from MBPT and hybrid TDDFT for the pristine molecules in vacuo is reported in the Supporting Information.…”
Section: Optical Propertiesmentioning
confidence: 99%